Geothermal System in Parang Wedang, Yogyakarta, Indonesia - Mochamad Iqbal; Bella Restu Juliarka (Journal of Engineering and Technological Sciences, 2022)
Geothermal manifestations in Parangtritis, Indonesia, known as Parang Wedang Hot Spring, indicate a geothermal system in the subsurface. This circumstance motivated our research to model the Parang Wedang geothermal system in order to determine its subsurface conditions. Geological mapping, the geophysical method, and geochemical analysis were integrated to produce a conceptual model of the Parang Wedang geothermal system. The study area consists of structural hills, karst hills, and eolian plains with andesite breccias, limestone, andesite, and sand deposits as lithological variations. The results of magnetic modeling indicate that the research area is associated with the presence of an andesite intrusion and shows a NE-SW trending geological structure that is thought to be a path for hydrothermal fluid to the surface. Geochemical analysis was performed at two hot springs with temperatures of 47 °C and 49 °C. Geothermometer calculation showed that the geothermal reservoir in Parang Wedang has a temperature of 100 to 120 °C, a depth of about 180 to 285 m, and can be classified as a low enthalpy geothermal system.